Calcium hydroxide apexification in immature lower premolar with dens evaginatus: a case report - Ahmad Bustami , Khairunnisa; Harun, Nor Asilah (2015)
Dens evaginatus can easily be traumatized, caused pulp necrosis and periapical pathosis before root maturation. Apexification is used traditionally to induce a calcific barrier at the apex of immature tooth. Calcium hydroxide has been widely accepted over a long period of time. Recently, revascularization has gained popularity in which blood clot act as a scaffold permitting the ingrowth of new tissue from periapical area in the absence of bacteria A healthy 13-year-old female patient was referred to our clinic. Upon clinical examination, fractured dens evaginatus viewed on the lower left premolar (35) tooth. A swelling at the buccal mucosa of tooth 35 was noted and it was tender to percussion. There was an evidence of periapical radiolucency with an open apex on a periapical radiograph. Calcium hydroxide apexification was performed and it was replaced three times in several weeks’ interval. A significant reduction in periapical radiolucency size and calcific apical barrier are evident radiographically seven months later. The tooth was then obturated with gutta percha. No signs and symptoms reported postoperatively. Although successful, this method relied on patient compliance for several recall appointment and it took a long time for apical barrier formation. Every method discussed in present literature has its pros and cons and demands appropriate case selection. Despite the popular methods nowadays such as revascularization, the conventional calcium hydroxide-based apexification is still relevant in cases where high cost and availability of materials are an issue, no bleeding in the canal space is obtained, and in case where post and core is indicated.